POULTRY IN A SCHOOL OF PHYSICAL EDUCATION IN SCHOOL CHILDREN IN SCHOOL UCRIA: A CASE STUDY (Fiep Bulletin - online, 2012)
The present work had as main objective to determine how the poultry is being worked in physical education classes in early childhood education in a private educational institution. The study is characterized as a case study is a descriptive qualitative approach, non-probabilistic sample of voluntary and intentional, consisting of a professor of poultry males. We used two techniques of direct observation in the intensive classes in capoeira, the unsystematic and non-participant. Extensive direct observation was used only one technique, the questionnaire. The proposal to teach capoeira in physical education is to make it not only a physical activity that has an end in itself, but also show that we can achieve goals that contribute to the development of children, to think of education through movement. During the observations, we found that the teacher seeks to work in all their classes, through movements of poultry, coordination, flexibility, balance, musicality, laterality, sense of time and space as well as socialization and integration between the children. It is recommended that the teacher of capoeira, which seeks to organize and plan their lessons about teaching children, as well as keep up to date look through the courses that address the subject poultry, pedagogical practice and child development.
Keywords: Capoeira; Physical Education; Childhood Education.